Caste and democratic politics in India - Shah, Ghanshyam (Delhi Permanent Black, 2004)
Contributed articles.
Includes bibliographical references (p. [437]-440).
Keywords: Caste -- Political aspects -- India; Democracy -- India; India -- Politics and government -- 1947-